«È per aiutare i giovani»? Note sulla produzione della copra sull’isola di Ouvéa (Kanaky-Nuova Caledonia) - Greta Maria Capece (Archivio Antropologico Mediterraneo)
Kanaky-New Caledonia is one of the Pacific post-colonial contexts experiencing the highest levels of internal inequalities, especially among young Kanaks, natives of the country, in relation to non-Kanaks, of both European and Pacific-Asian origin. As part of an ethnography carried out between February 2020 and October 2020, the article aims to present, within the first group, some notes on the mechanisms of reproduction of inequalities, through the delineation of the social and labour trajectories of young copra producers on the island of Ouvéa. For these purposes, a case study on one particular stage of the chain, namely drying, will be presented.